Pengembangan Media Kincir Angin Berbasis Baterai sebagai Alat Peraga Pembelajaran Energi dan Perubahannya - Sarah Aulia Akbar, Siti; Nurapidah, Nurapidah; Agung Tunny, Chairul; Nasharuddin, Nasharuddin (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
This research aims to design and develop a battery-based windmill diorama as a teaching aid for science education to improve student understanding and provide an effective alternative learning media. The research method used is the Research & Development concept, employing the 4-D model which includes the stages of define, design, develop, and disseminate. The focus of the research is on the topic of energy and its transformations for fourth-grade elementary school students. The research instrument used is an evaluation by experts to assess the quality of the media based on predetermined criteria. The results of the study indicate that the battery-based windmill diorama received an evaluation score of 91%, which falls into the